(untitled) (Annals of Medical Research, 2023)
Aim: Severe complications such as bacteremia and bile duct infection may arise following percutaneous transhepatic biliary drainage (PTBD). The objective of this study was to examine the factors that contribute to mortality and compare the differences between patients with positive blood and biliary drainage cultures following PTBD. Materials and Methods: This retrospective study was conducted from January 2017 to February 2019. The study was carried out at a hospital where 547 percutaneous transhepatic biliary drainage (PTBD) procedures were performed during this period. The study evaluated patients who showed no signs of infection prior to the procedure. The patients were categorized into three groups based on culture results: the first group with only bacteremia, the second group with only positive bile drainage culture, and the third group with both bacteremia and positive bile drainage culture. This study compared the clinical and laboratory parameters among these groups and examined the culture results in a high-resistance environment. Results: Ninety patients either developed bacteremia, bile duct infections, or both in this study. The laboratory results revealed that patients with bacteremia exhibited a notably higher serum level of alanine aminotransferase. (ALT) (p=0.001). Independent risk factors associated with 30-day mortality after PTBD included elevated neutrophil counts, lipase levels, and the presence of carbapenem-resistant isolates (p=0.01, p=0.01, and p=0.04, respectively). Gram-negative organisms were present in 71.2% of the cases; Escherichia coli was the most common species (28.1%) followed by Enterococcus faecium (18.1%), Klebsiella pneumoniae (15.8%) and Pseudomonas aeruginosa (9.9%). Of the cultured gram-negative bacteria, 41.8% (51 isolates) were found to be positive for extended spectrum beta-lactamases, while 15.8% (27 isolates) of the isolates showed carbapenem resistance. Conclusion:The sole distinguishing factor observed among the three groups was the elevated level of alanine aminotransferase. Consequently, bacteremia and bile culture positive patients should be treated with the same care. Independent risk factors associated with mortality included elevated neutrophil counts, lipase levels, and the presence of carbapenem-resistant isolates. Finally, the choice of antibiotic prophylaxis should be reviewed according to the antimicrobial resistance profiles.